FACTORS RELATED TO NURSE’S COMPASSION SATISFACTION, BURNOUT, AND SECONDARY TRAUMATIC STRESS IN PEDIATRIC CARE UNIT RSUP DR. SARDJITO YOGYAKARTA - Dwi Aprilina Andriani; Anik Rustiyaningsih; Fitri Haryanti (Belitung Nursing Journal, 2017)
Background: Pediatric nurses are susceptive with stress related to their work. It happens because they take care children who experience the disease and emotional and psychological pressure, so it can make the risk of negative symptoms related with compassion satisfaction, burnout, secondary traumatic stress. Compassion satisfaction, burnout, secondary traumatic stress has an impact not only for them, but also for the quality of treatment. Objective: To identify related factors to nurse’s compassion satisfaction, burnout, and secondary traumatic stress in pediatric care unit. Methods: This study was a descriptive analytic study with cross sectional design. The sample of this study was 107 pediatric nurses of RSUP Dr. Sardjito Yogyakarta Indonesia. The sampling techniques used proportional random sampling. The data were collected from February-March 2017 using the professional quality of life questionnaire fifth version. The data were analyzed using Chi-square, Mann-Whitney, and ordinal regression. Results: 44.9% nurses had a moderate compassion satisfaction, 52.3% nurses had a moderate burnout, and 43% had a moderate secondary traumatic stress. The work unit had p <0.05 and β value 0.945, indicated that the work unit had a significant correlation to the secondary traumatic stress. Age, work position, sex, marital status, interpersonal relationships with colleagues and supervisor, pay satisfaction, and average working hours had p > 0.05, which indicated that these factors had no correlation to compassion satisfaction, burnout, secondary traumatic stress. Conclusion: The work unit was the only related factor to the nurse’s secondary traumatic stress in the pediatric care unit and there were no factors related to compassion satisfaction and burnout.